Learning and Using Abstract Words: Evidence from Clinical Populations. (19th December 2017) - Lorusso, Maria Luisa; Burigo, Michele; Tavano, Alessandro; Milani, Anna; Martelli, Sara; Borgatti, Renato; Molteni, Massimo
Abstract : It has been shown that abstract concepts are more difficult to process and are acquired later than concrete concepts. We analysed the percentage of concrete words in the narrative lexicon of individuals with Williams Syndrome (WS) as compared to individuals with Down Syndrome (DS) and typically developing (TD) peers. The cognitive profile of WS is characterized by visual-spatial difficulties, while DS presents with predominant impairments in linguistic abilities. We predicted that if linguistic abilities are crucial to the development and use of an abstract vocabulary, DS participants should display a higher concreteness index than both Williams Syndrome and typically developing individuals. Results confirm this prediction, thus supporting the hypothesis of a crucial role of linguistic processes in abstract language acquisition. Correlation analyses suggest that a maturational link exists between the level of abstractness in narrative production and syntactic comprehension.